Investigation on women's space in masjid architecture: case study of selected masjids in Malaysia - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Jahn Kassim, Puteri Shireen (2014)
Muslim women participation in masjid, a place where the community congregates interacts and a place for education, is allowed but non-compulsory in Islam. In Malaysia, women as part of the community frequented the masjid for different activities at a daily basis. Therefore, their presence and needs should form an integral part of the masjid space planning and design provisions. However, from observations and personal experience, the design of masjids is frequently gender insensitive as there is no definite guideline on space provision for women. This paper examines the issues on space planning of masjid in relation to the requirements for women. The objectives of this paper are; (i) to investigate how spaces and requirements for women in the masjid are derived from the original sources of Islam (Quran and Hadith); and (ii) how its’ essence has been applied in masjid in Malaysia. Qualitative method namely analytical analysis of layout and observation was adopted for this research due to its exploratory nature. Data collected are analysed through comparative method to derive trends on planning and design on selected traditional and contemporary masjid in Malaysia. Findings indicate that in general the design of the masjid is gender insensitive towards women such as obscured access; temporal nature of prayer space; location of ablution area away from the prayer area; and inaccessibility for the disable and elderly women.